Endogenous digoxin-like factor contributes to the elevation of systemic resistance in rats exposed to high salt intake from prepuberty - Zicha, J; Kunes, J; Stolba, P (Journal of hypertension. Supplement, 1985)
The acute administration of anti-digoxin serum (ADS) caused a pronounced blood pressure decrease only in those hypertensive rats that were treated with desoxycorticosterone acetate (DOCA) and 1% saline from prepuberty. This was due to a rapid decrease in systemic resistance which was partially compensated by increased cardiac output. There were no similar effects of ADS in rats treated in the same manner in adulthood only. Different mechanisms might be responsible for blood pressure elevation induced by high salt intake in youth or in adulthood. The participation of endogenous digoxin-like factor in the maintenance of elevated systemic resistance in DOCA-salt hypertensive rats is a typical case.
Keywords: hypertenze; Male; Rats, Wistar; hemodynamika; Saponins; Animals; saponiny; potkani Wistar; digoxin; Cardenolides; Desoxycorticosterone; krevní tlak; Sodium, Dietary; mužské pohlaví; cévní rezistence; krysa rodu Rattus; Blood Pressure; Blood Proteins; sodík dietní; deoxykortikosteron; Rats; pohlavní dospělost; Sexual Maturation; zvířata; kardenolidy; Hemodynamics; Digoxin; krevní proteiny; Hypertension; Vascular Resistance